ANALISIS UNSUR INSTRINSIK DAN NILAI MORAL CERPEN “KEMARAU” KARYA ANDREA HIRATA - Annisa Novianti; Siti Mila Anggraeni (Populer: Jurnal Penelitian Mahasiswa, 2022)
This article discusses social criticism in a short story entitled "Kemarau" by Andrea Hirata. This article will focus on mimetic approach research on things or events in short stories related to social criticism in the short story entitled "Kemarau", namely: (1) criticism of political issues, when people feel disappointed about government promises that are not implemented (2) ) criticism of the economy, where when a group of people who live on the outskirts cannot feel the development and progress of infrastructure like in big cities (3) criticism of the negligence factor of the government when it has occupied its position. The government seems to have forgotten the promises it made before taking up its post. From the short story, it can be understood that literary works do not only display positive impressions or messages but can contain absolute things such as criticizing or satirizing.